Tumor-Infiltrating Lymphocytes and Neutrophils and Their Location in Canine Mammary Neoplasms with a Solid Arrangement: A Prognostic Factor? - Mayra C. Flecher; Marina P. Reys; Débora Balabram; Karen Y. R. Nakagaki; Geovanni D. Cassali (Animals)
In canine mammary neoplasms, greater inflammation is associated with higher histological grade, lymphatic invasion, and metastases. This retrospective study assessed the density of peri- and intratumoral tumor-infiltrating lymphocytes (TILs), tumor-associated neutrophils (TANs), and CD3+ and CD79+ lymphocytes in canine mammary neoplasms with a solid arrangement, and associated such data with histological types, immunophenotype, prognostic factors, cyclooxygenase-2 (Cox-2) expression and overall and cancer-specific survival. Sixty-one neoplasms with a solid arrangement were classified as malignant myoepitheliomas (6/9.8%), solid papillary carcinomas (8/13.1%), carcinomas with a solid pattern (9/14.8%), basaloid carcinomas (BC) (19/31.1%), and malignant adenomyoepitheliomas (19/31.1%). Intra- and peritumoral TILs, TANs, and TCD3+ and BCD79+ lymphocytes were counted, and based on the resulting median, the neoplasms were divided into low or high cell infiltration. BCs had the lowest density of intratumoral TILs (p = 0.02), and luminal B neoplasms showed a significantly higher density of intratumoral TCD3+ than luminal A cases. Neoplasms with a higher density of peritumoral CD3+ and CD79+ had significantly greater proliferative activity. High infiltration of intratumoral BCD79+ lymphocytes was related to nodal metastasis (p = 0.03). Intratumoral TILs and TCD3+ were associated with shorter survival time. Therefore, intratumoral lymphocyte infiltration is possibly an important feature in the progression of cancer and influences the survival in bitches with solid arrangement neoplasms.